Cellular mosaicism for X‐linked polymorphisms and IRAK1 expression presents a distinct phenotype and improves survival following sepsis. Issue 3 (5th November 2013) - Chandra, Rachna; Federici, Stephanie; Németh, Zoltán H.; Csóka, Balázs; Thomas, James A.; Donnelly, Robert; Spolarics, Zoltán
Abstract : X chromosome cellular mosaicism for IRAK1 expression in mice increases circulating B cell numbers and preconditions for improved sepsis outcome. Abstract : ChrX cellular mosaicism for X‐linked genetic polymorphisms in females versus the single ChrX representation in males denotes a genetic difference, which may contribute to gender bias in the inflammatory response. This hypothesis was tested in female F1 offspring of consomic mice (BL6J‐ChrX A/J /NaJ) that were homokaryotic or mosaic for the active BL6 and AJ ChrXs or for IRAK1 deficiency linked to the BL6 ChrX. Sepsis was initiated by CLP. IRAK1‐deficient and IRAK1‐mosaic mice showed similar protection from sepsis‐induced mortality and reduced IL‐6 and IL‐10 release compared with WT. BM cellularity and blood B cell counts were increased in naive IRAK1‐mosaic mice compared with WT‐mosaic or IRAK1‐deficient animals. Sepsis‐induced BM cell depletion was greater in IRAK1‐mosaic mice compared with WT‐mosaic or IRAK1‐deficient subjects, whereas splenic B and T cell depletion was less in IRAK1‐mosaic and IRAK1‐deficient than WT‐mosaic mice. Skewing toward AJ or BL6‐ChrX‐expressing cells was assessed by testing allele‐specific expression of strain‐variant Xkrx and BTK genes. In naive IRAK1‐mosaic mice, BM and blood cells with the active BL6‐ChrX, were greater than cells expressing the AJ‐ChrX (cell ratio 2.5 in IRAK1‐mosaic; 1.5 in WT‐mosaic mice). Sepsis decreased cell ratios more in IRAK1‐mosaic than in WT‐mosaic mice. The study reveals functional variability in cellular mosaicism for IRAK1 expression and natural X‐linked polymorphisms during sepsis. Mosaicism for IRAK1 expression is accompanied by skewing toward deficient immune cell populations, producing a phenotype that is preconditioned for improved sepsis outcome similar to that observed in IRAK1 deficiency.